Adaptive Hysteresis Current Control Of A Pwm Inverter At Constant Modulation Frequency Applied To Shunt Active Power Filters - Rondineli Rodrigues Pereira; Carlos Henrique da Silva; Luiz Eduardo Borges da Silva; Germano Lambert-Torres; Bimal K. Bose (Eletrônica de Potência, 2010)
This paper proposes a novel adaptive hysteresis current control strategy of a voltage-fed PWM inverter, where the switching frequency always remains constant and the harmonic ripple is minimum, irrespective of dc link voltage fluctuation and load parameter variation. The developed algorithm works well for single-phase as well as multi-phase inverters, although single-phase inverter operation, particularly in active harmonic filter mode, is emphasized in this paper. The algorithm uses fuzzy logic-based current error compensation, and it is simple to implement and does not involve any hysteresis-band calculation. The control strategy has been implemented digitally with a high-speed digital signal processor (TI-TMS320F2812). The proposed scheme has been thoroughly evaluated in laboratory by simulation as well as in experimental studies on a single-phase inverter, and its performance was found to be excellent.